In the Supreme Court of the United States, Eleanor McCullen, Jean Zarrella, Gregory A. Smith, Mark Bashour, and Nancy Clark, petitioners, v. Martha Coakley, Attorney General for the Commonwealth of Massachusetts, et al., respondents on writ of certiorari to the United States Court of Appeals for the First Circuit : brief of civil rights organizations as amici curiae in support of respondents and affirmance / Stephanie Toti, counsel of record. - Toti, Stephanie (Legal Printers LLC, 2013)
At issue is the constitutionality of a Massachusetts law imposing a demonstration-free buffer zone around abortion clinics. Amici support petitioners in arguing that the law violates the First Amendment rights of abortion protestors to provide, and women to receive, information about abortion.